Socioeconomic achievement gaps in science and social studies in Colombia: an assessment of factors affecting school achievement - Cabra Hernández, Hans Walter (Frontiers in Education, 2025)
This paper investigates the factors associated with socioeconomic achievement gaps in science and social studies among high school students in Colombia and explores the implications for Education for Sustainable Development (ESD). Utilizing a comprehensive cross-cohort dataset from the SABER 11 standardized examination for the period 2017–2023, which included sample sizes ranging from 330,152–377,354 students, a four-level multilevel modeling approach was employed. Data were aggregated at the student, school, municipality, and department levels. The analysis reveals that school characteristics are the most significant factors contributing to the achievement gap, with the length of the school day and school location emerging as key predictors of academic performance in these subjects. Furthermore, the study confirms the persistence of gender and ethnic-based academic disparities. Individual socioeconomic factors, specifically insufficient nutrition, student employment, and a lack of reading habits, were found to be negatively associated with academic achievement. By shedding light on these disparities in subjects critical for ESD in the Colombian context, this research provides valuable evidence for informing and strengthening educational policies aimed at fostering more equitable learning outcomes and advancing sustainable development practices.